The Effect of Brand Image, Social Media Marketing, Customer Engagement, and Service Quality on Purchase Intention - Mu'is, Abdul; Saputra, Asep Dana (International Journal of Business, Law, and Education, 2026)
This paper sets out to investigate the influence of brand image, social media marketing, customer engagement, and service quality on purchase intention. For the collection of data, the quantitative research approach with an explanatory model was adopted. The findings from the multiple regressions revealed the positive impacts of social media marketing, customer engagement, service quality, and brand image on the purchase intention. It was revealed that the service quality exerts the strongest positive influence, followed by customer engagement, brand image, and then social media marketing. It may be concluded that the purchase intentions of the consumers have been affected not only by the promotional activities conducted by the organizations, along with the perceptions based on the marketing, but by the service quality, as well. This paper helps to bridge the existing gaps in the marketing literature by providing an empirical determination regarding the impacts exerted by the combination of marketing, digital marketing, consumer engagement, and service quality, and hence helps the marketers by providing practical knowledge for developing appropriate strategies for the enhancement of the consumers' purchase intentions.